2022
DOI: 10.1155/2022/4156489
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Systemic Immune-Inflammation Index and All-Cause Mortality in Acute Ischemic Stroke Patients: Analysis from the MIMIC-IV Database

Abstract: Purpose. Acute ischemic stroke (AIS) is a devastating disease and remains the leading cause of death and disability. This retrospective study aims to investigate associations between systemic immune-inflammation index (SII) and all-cause mortality in patients with AIS. Patients and Methods. We used the data from Medical Information Mart for Intensive Care IV. A total of 1,181 patients with acute ischemic stroke (AIS) were included. Systemic immune-inflammation index (SII) was calculated as platelet count (/L) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…18 Consistent with their research, our study confirmed the predictive value of initial SII in clinical outcomes of patients with AIS again and discovered that SII is also relevant with END and 3-month death. In line with our results, Wu et al 19 reported that elevated SII increased the risk of 30-day all-cause mortality in patients with AIS. In another thrombolysis-related research conducted by Topcuoglu et al, 20 patients with 3-month favorable functional outcomes had lower neutrophil-to-lymphocyte ratio and SII, but the results did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…18 Consistent with their research, our study confirmed the predictive value of initial SII in clinical outcomes of patients with AIS again and discovered that SII is also relevant with END and 3-month death. In line with our results, Wu et al 19 reported that elevated SII increased the risk of 30-day all-cause mortality in patients with AIS. In another thrombolysis-related research conducted by Topcuoglu et al, 20 patients with 3-month favorable functional outcomes had lower neutrophil-to-lymphocyte ratio and SII, but the results did not reach statistical significance.…”
Section: Discussionsupporting
confidence: 93%
“…Jia L et al found a similar J-shaped relationship in patients with acute kidney injury [12]. However, a recent study found a linear positive association in patients with acute ischemic stroke [37]. The controversy may be related to the cutoff values for the grouping and different study populations.…”
Section: Discussionmentioning
confidence: 97%
“…The SII may be useful in elucidating the role of inflammation, thrombocytosis, and immunity interaction in the development of acute ischemic stroke. 45…”
mentioning
confidence: 99%